Gastrodin attenuates rheumatoid arthritis by targeting KAT8 to inhibit the lactylation of H3K9 - Yufang Dai; Shunshun Wang; Shunshun Wang; Jiayi Luo; Huiming Yu; Huiming Yu; Qianqian Du; Qianqian Du; Shuwan Hou; Minfu Liu; Shan Jiang; Shan Jiang; et al. (Frontiers in Pharmacology)
Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by synovial inflammation and joint destruction, with limited therapeutic options. This study investigated the therapeutic potential of gastrodin (GAS), a natural phenolic glycoside derived from Gastrodia elata, in targeting lysine acetyltransferase 8 (KAT8) to suppress histone H3K9 lactylation (H3K9la), a novel post-translational modification linked to inflammatory responses.Methods: The therapeutic effect of GAS on RA was verified by constructing RA models in vivo and in vitro. Molecular docking, surface plasmon resonance (SPR) assays, overexpression and silencing experiments were used to verify the results.Results:In vitro experiments demonstrated that GAS (10–20 μM) significantly inhibited lipopolysaccharide (LPS)-induced expression of pro-inflammatory cytokines (IL-6, MMP1, MMP13) in fibroblast-like synoviocytes (FLS) and THP-1 macrophages by downregulating glycolysis and lactate production. Molecular docking and surface plasmon resonance (SPR) assays confirmed KAT8 as a direct target of GAS, with a dissociation constant (KD) of 413.72 μM. Overexpression and silencing experiments revealed that GAS destabilized KAT8, thereby reducing H3K9la levels. In vivo, GAS (20 mg/kg) ameliorated joint swelling and synovial hyperplasia in a Sprague-Dawley rat adjuvant-induced arthritis (AIA) model, correlating with decreased H3K9la and IL-6 expression.Discussion: These findings establish GAS as a promising therapeutic agent for RA by modulating KAT8-mediated histone lactylation, providing new insights into epigenetic regulation of inflammation.